133k views
0 votes
Rs - t= us + v; solve for s

User Blins
by
4.4k points

2 Answers

4 votes

Answer:

s = (v + t) / (r - u).

Explanation:

rs - t = us + v

rs - us = v + t

s(r - u) = v + t

s = (v + t) / (r - u).

User Nachiket Gohil
by
5.5k points
2 votes

Answer:


s=(v+t)/(r-u)

Explanation:

Given : Expression
rs-t=us+v

To find : Solve the expression for s?

Solution :

Step 1 - Write the expression,


rs-t=us+v

Step 2 - Add t both side,


rs=us+v+t

Step 3 - Take like terms together,


rs-us=v+t

Step 4 - Take s common,


s(r-u)=v+t

Step 5 - Divide r-u both side,


s=(v+t)/(r-u)

User Dwenaus
by
5.1k points